Behind the GATE Experiment: Evidence on Effects of and Rationales for Subsidized Entrepreneurship Training - Robert W. Fairlie; Dean Karlan; Jonathan Zinman (Institute for the Study of Labor (IZA), 2014)
Theories of market failures and targeting motivate the promotion of entrepreneurship training programs and generate testable predictions regarding heterogeneous treatment effects from such programs. Using a large randomized evaluation in the United States, we find no strong or lasting effects on those most likely to face credit or human capital constraints, or labor market discrimination. We do find a short-run effect on business ownership for those unemployed at baseline, but this dissipates at longer horizons. Treatment effects on the full sample are also short-term and limited in scope: we do not find effects on business sales, earnings, or employees.
Keywords: L26; J24; 330; entrepreneurship; training; random experiment; evaluation; self-employment